1997
DOI: 10.1002/(sici)1097-0231(19971015)11:15<1643::aid-rcm14>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Study of decomposition of sulphur hexafluoride by gas chromatography/mass spectrometry

Abstract: When electrical discharges occur in sulphur hexafluoride gas (SF 6 ) lower fluorides are produced within the discharge, and they in turn react readily with impurities, insulators and the electrodes. The final stable compounds formed include sulphur oxyfluorides and sulphur oxides. The aim of the present work was to optimize an analytical method for determining the decomposition products, and finding the dependence of the reaction route followed on the reaction conditions (input energy, contaminants present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Typically the analytical system showed no blanks for SO 2 F 2 . Previously used analytical methods including gas chromatography with various detectors achieved detection limits in the 1‐ to 20‐ppm range [ Kóréh et al , 1997; Pradayrol et al , 1997], except for Qu et al [2000], who reported a detection limit of 0.4 ppt by GC‐ECD (electron capture detector).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically the analytical system showed no blanks for SO 2 F 2 . Previously used analytical methods including gas chromatography with various detectors achieved detection limits in the 1‐ to 20‐ppm range [ Kóréh et al , 1997; Pradayrol et al , 1997], except for Qu et al [2000], who reported a detection limit of 0.4 ppt by GC‐ECD (electron capture detector).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Further emissions to the atmosphere may result from the use of SO 2 F 2 in the semiconductor industry as a plasma cleaning gas [ Hobbs and Hart , 2005] and in the magnesium industry as a blanketing gas to replace sulfur hexafluoride (SF 6 ), which has an exceptionally large global warming potential. Trace amounts of SO 2 F 2 are also formed from SF 6 by electrical discharges in transformers [ Kóréh et al , 1997; Pradayrol et al , 1997]. Symonds et al [1988] concluded that SO 2 F 2 emissions from volcanoes are probably extremely small.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, discovering SF 6 decomposition products and dealing with insulation defects in a timely manner have great importance. To date, several methods such as gas chromatography, mass spectrometry and Fourier transform infrared spectroscopy, are suggested to detect SF 6 products [ 10 , 11 ]. However, these methods are either inaccurate or complicated, so none of them are used in detecting SF 6 decomposition products.…”
Section: Introductionmentioning
confidence: 99%
“…In various discharge environments [2][3][4][5][6][7][8][9][10][11][12][13], SF 6 can be dissociated into lower sulfur fluorides in a low-to high-temperature reactor via a stepwise process: SF x + e → SF x−1 + F + e (6 x 1) [14].…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate species of dissociation, SF x [15], tend to recombine rapidly to SF 6 or reform into the highly toxic Table 1 Threshold limit value (TLV) of the concentration of byproducts possibly produced from the abatement of SF 6 [16] Compound TLV or TWA a Compound TLV or TWA a S 2 F 10 0.01 ppm COF 2 2 ppm SF 4 0.1 ppm (ceiling) HF 3 ppm SOF 2 0.7 ppm SO 2 F 2 5 ppm SiF 4 0.8 ppm NO 25 ppm F 2 1 ppm SOF 4 -b SO 2 2 ppm a TWA: time-weighted average. b (-) No data.…”
Section: Introductionmentioning
confidence: 99%